Copula autoregressive methodology for the simulation of wind speed and direction time series (2016)
"This paper applies a copula autoregressive methodology for simulating hourly wind speed and direction time series considering the serial and between-series dependence. This methodology allows non-linear and asyrnrnetric modelling of the series, which translates to a better replication Of the statistical Of the time series Of historical data used. Also it allows to separate Out the modelling Of the temporal dependence from the marginal behaviour Of the time series. Results showed that the copula autoregressive methodolouy is able to reproduce most of the linear and non-linear characteristics observed on the original series". -- Tomado del resumen.